Effects of Inhaled Corticosteroids on Lung Function in Children With Post-infectious Bronchiolitis Obliterans in Remission - Zheng, Haoqi; Yu, Xiuhua; Chen, Yuquan; Lin, Wenying; Liu, Li (Frontiers in Pediatrics, 2022)
Background Post-infectious bronchiolitis obliterans (PIBO) is a rare and irreversible chronic obstructive pulmonary disease with no specific treatment, especially for patients with PIBO in remission. In this study, we evaluated the effects of continuous inhaled corticosteroids (ICSs) and intermittent ICSs on lung function in the remission of PIBO. Methods This was a retrospective study, and all the subjects we included were divided into continuous ICS group and intermittent ICS group according to treatment regimens. Patients in continuous ICS group received continuous ICSs (2 times a day), and patients in intermittent ICS group received intermittent ICSs (inhaled corticosteroids after acute respiratory tract infection or wheezing). Different lung function tests were performed at different ages. Tidal breathing lung function tests were performed in patients with PIBO aged ≤ 5 years, and the lung ventilation function test and the bronchial dilation test were performed in patients with PIBO aged more than 5 years. Lung function was assessed at the beginning of follow-up and at the end of follow-up (1 year of ICSs). Results After 1 year of ICSs, patients aged more than 5 years, forced vital capacity (FVC), and forced expiratory volume in 1 s (FEV1) were significantly higher than at the beginning of follow-up. After 1 year of ICSs, the difference in VT/Kg, TPTEF/TE, and VPEF/VE between the end and the beginning of follow-up in continuous ICS group shows an upward trend. But those showed a downward trend in intermittent ICS group. FVC, FEV1, and maximal mid-expiratory flow velocity 25–75% (MMEF25–75%) of continuous ICS group were significantly higher than at the beginning of follow-up. The difference in FEV1 and MMEF25–75% between the end of follow-up and the beginning of follow-up in continuous ICS group was significantly higher than that in intermittent ICS group. A total of 52.94% of patients with PIBO aged more than 5 years were positive for bronchial dilation tests. Conclusion Inhaled corticosteroids can effectively improve lung function and relieve airway obstruction in patients aged more than 5 years in PIBO remission, especially continuous ICSs. Patients with PIBO may have reversible airflow limitations.